IT Technologies, Distance Learning, Electronic Digital in Teaching Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the teaching methodology, especially the role of IT technologies in the teaching of foreign languages and it is useful aspects are deeply studied. The discussion includes the role of distance education and its importance and methods within the framework of foreign language teaching and integrates the ideas of different  teaching methodologies. It emphasizes the importance of electronic digital education and its interdisciplinary nature. Conclusion the words provide a comprehensive overview of the topic, highlighting the contribution of IT technologies to distance learning and learning methods.